Reducing hate through multicultural education and transformation - Obiakor, Festus E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"Reducing Hate through Multicultural Education and Transformation is a book that reminds us that we live in a complex world; and at micro and macro levels, the demography is changing and people are worried about the current state of affairs, their future, and the future of their children. At local, national, and global levels, there appears to be unsteadiness, crises, and struggles in our economies, politics, and societies. Disruptions, disasters, and deaths are visible at all spectra of our lives; and our leaders seem unready, unwilling, underprepared, and unprepared to bring us together to solve our problems for the common good. Even when we make efforts to respond to human differences and multicultural valuing, they seem to be half-baked cakes that are unready for consumption; and there continues to be visible hateful actions that devastate our sacred existence. Sadly, these hateful actions have filtered into our families, schools, communities, nation, and world. Funny enough, we talk about our problems and sweep them under the rugs; and we pretend to solve them by engaging in phony community relations, fraudulent multiculturalism, and unreasonable "wokeness" to masquerade our inefficiency, inflexibility, nonchalance, prejudice, and jaundiced views. In Reducing Hate through Multicultural Education and Transformation, I reiterate how the complexity of our world challenges us to understand how we got here and what we plan to do to respond to our future. I argue for paradigm and power shifts in the ways we live, interact, collaborate, consult, and cooperate with each other. I posit that our economic, political, social, and educational worlds have to change or we will be consumed by change. As it appears, the more things change, the more they remain the same. Rather than build and develop our realities, we continue to hope that our problems will disappear. But, problems unsolved continue to wait for us until we solve them. Consider these glaring examples! The world was confused and shocked when President Vladimir Putin of Russia ordered the hateful invasion of Ukraine that caused disruptions, disasters, and deaths. In the midst of the confusion and shock, the world continued to give supports to Ukraine in defending its territorial integrity. But, the corrosive consequences of the invasion reverberate! And, our recent encounter with COVID has shown that we live in two worlds instead of ONE world. While the Western world (e.g., United States, Great Britain, France, Canada, etc.) worked hard to treat it, developing countries (e.g., African nations, Caribbean nations, Latin American nations, etc.) were confused and waited for help to deal with it. It has become clear that there continues to be differences on how the intensities of economic disparities, political unrests, and social instabilities are felt in developed and developing countries. Is it any surprise that citizens of developing countries consistently look for ways to migrate or immigrate to other more developed countries? On the other hand, is it any wonder that citizens of developed countries worry about "strange" people who come into their beloved countries to disrupt their equilibrium? The consequences of these different perspectives manifest themselves in increased hatred, nativism, nationalism, racism, prejudice, bias, xenophobia, religious dogmatism, cultural alienation, linguistic supremacy, disenfranchisements, disadvantages, and disillusionments, to mention a few. Naturally, when people feel overwhelmed with problems, they resort to anger and hate. It is clear that our educational problems have become endemic; and, it is also clear that Reducing Hate through Multicultural Education and Transformation provides cutting edge solutions for innovative educators and leaders. Yes, hate is a controversial construct that is rarely researched, studied, and discussed in education. The reason is that teachers and related professionals are supposedly liberal---they cannot hate their culturally and linguistically diverse (CLD) students, parents, and colleagues. And, the lingering question is, Can a teacher who is always liberal be also hateful? This question seems legitimate; and, to answer it, we look deeper into the traditional political presumption. The reality is that White educators and related professionals who dominate the educational profession are human-beings who live in their respective well-protected White dominated communities. If not, why should many CLD individuals continue to experience hateful misidentifications, misassessments, miscategorizations, misplacements, and misinstructions in school settings and programs? And, why should disproportionate placements of CLD learners with special education needs, gifts and talents, and emotional/behavioral problems continue to be burning hateful issues in education? This book provides outside-the-box solutions!"-- Provided by publisher.
Keywords: Multicultural education -- Social aspects.; Multiculturalism.; Cultural relations.; Education -- Multicultural Education.; Educational strategies and policy: inclusion.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books